1992
DOI: 10.1111/j.1469-8137.1992.tb00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of symbiotically fixed nitrogen from berseem (Trifolium alexandrinum L.) to maize via vesicular—arbuscular mycorrhizal hyphae

Abstract: SUMMARYIn order to examine wbetber bypbae of VA mycorrbizal fungi may aid tbe transfer of symbiotically fixed nitrogen from a legume to a non-legume, tbe roots of berseem plants inoculated with the VAM fungus Glomus intraradices and Rhizobium leguminosarum biovar. trifolii (strain RCR 5) were separated by a 2 cm root-free zone from tbe roots of maize plants. A 40 (xm pore size nylon net allowed VAM bypbae to pass tbrougb tbe root-free zone but prevented root penetration. Replacement of tbis net by a 0-45 ixm p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 43 publications
(42 reference statements)
4
68
0
3
Order By: Relevance
“…Previous work has demonstrated that both ectoand endomycorrhizas are able to mediate N-transfer between plants (Haystead, Malaczuk & Grove, 1988; Barea, Azcon & Azcon-Aguilar, 1989;Bethlenfalvay etal., 1991 ;Arnebrant e( a/., 1993;Frey & Schuepp, 1994). However, Hamel et a!.…”
Section: Discvssionmentioning
confidence: 99%
“…Previous work has demonstrated that both ectoand endomycorrhizas are able to mediate N-transfer between plants (Haystead, Malaczuk & Grove, 1988; Barea, Azcon & Azcon-Aguilar, 1989;Bethlenfalvay etal., 1991 ;Arnebrant e( a/., 1993;Frey & Schuepp, 1994). However, Hamel et a!.…”
Section: Discvssionmentioning
confidence: 99%
“…Nevertheless, the mycorrhizal contribution to the N nutrition of plants in the field might be substantial, especially in dry soils as shown by Tobar et al (1994) or in acid soils, where N occurs mainly in the less-mobile ammonium form. Investigations on AMF-mediated N transfer from an N-fixing plant species to a nonfixing plant species is another potential field of application (Bethlenfalvay et al, 1991 ;Frey & Schu$ epp, 1992 ;Tomm et al, 1994). To avoid problems in the calculations of N transfer due to N mineralized during the experiment, we suggest that only quartz sand should be used as a plant growth substrate, not a mixture that includes field soil (Frey et al, 1998).…”
Section: mentioning
confidence: 99%
“…The one exception that did not contain the tracer was a non-mycorrhizal plant species. Transfer of phosphorus (P) and nitrogen (N) between plants via hyphal links has also been reported for many plants in pot culture and in glasshouse conditions [7][8][9][10]. Most of the experiments were designed to investigate transfer in one direction despite the possible occurrence also of transfer in the opposite direction.…”
Section: Introductionmentioning
confidence: 99%